2019
DOI: 10.1080/1828051x.2019.1704634
|View full text |Cite
|
Sign up to set email alerts
|

Response of broilers to gradual dietary protein reduction with or without an adequate glycine plus serine level

Abstract: This study was aimed to probe broiler responses to the maintenance of adequate level of glycine plus serine in low crude protein (CP) diets by glycine (Gly) addition from 8 to 42 days of age. A total of 1152 7-d-old birds were divided into 8 groups and fed with one of the following diets: (I) normal CP diet; (II, III vIV V) diets with 1.5%, 3%, 4.5% and 6% points less CP than normal diet, respectively; (VI, VII, VIII) diets with 3%, 4.5% and 6% points reduced CP than the normal CP diet, respectively, and added… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
4
7
0
1
Order By: Relevance
“…Moreover, glycine improved nutrient utilization and protein synthesis, thus improving growth performance [ 23 ]. This statement supports our judgment that glycine supplementation in a reduced protein diet reduced the negative effect on growth performance, which is also in agreement with Wang et al, 2020 [ 24 ]. Also, L-methionine could also be a reason for acceptable growth performance.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, glycine improved nutrient utilization and protein synthesis, thus improving growth performance [ 23 ]. This statement supports our judgment that glycine supplementation in a reduced protein diet reduced the negative effect on growth performance, which is also in agreement with Wang et al, 2020 [ 24 ]. Also, L-methionine could also be a reason for acceptable growth performance.…”
Section: Discussionsupporting
confidence: 93%
“…Decreased abdominal fat and increased keel bone length. This results are in agreement with the finding of Wang et al (2020) who found that there were no significant effects due to 1.5% of dietary CP reduction on carcass traits of broilers at 21 and 42 day of age. Lowering dietary CP level by 3% significantly increased abdominal fat percentage of birds on d 42.…”
Section: Carcass Traitssupporting
confidence: 93%
“…was the best FCR during the overall period. These results are in agreement with the finding of Wang et al (2020) who found that adding glycine to broiler chicks diet to 2.32% total glycine and Serine with a 3% reduction of crude protein level normalized the growth performance of broiler chicks and significantly improved feed conversion ratio during starter and the overall periods as standard protein diet chicks. Supplementation of glycine to the diet with a 4.5% CP reduction restored to the standard levels both of feed conversion ratio (starter period), final Body weight and overall average daily weight gain.…”
Section: Productive Performancesupporting
confidence: 92%
See 1 more Smart Citation
“…These results are likely due to broilers eating to satisfy a certain nutrient need like previously recorded for the LCP-fed chicks from 0 to 14 d and such nutrients may include the lower (7.4-8.3%) analyzed tGly+Ser, Trp, or Leu from 28 to 39 d. From 0 to 48 d, broilers fed the LCP88 diet (2.38% unit average analyzed CP reduction) had the highest FCR and linear, but not quadratic, improvements in FCR were observed when increasing dietary tGly + Ser. Similarly, other studies have shown that the addition of Gly had the most impact on improving FCR ( Waguespack et al, 2009b ; Berres et al, 2010 ; Kriseldi et al, 2017 ), possibly by improving nutrient utilization and protein synthesis via enterocyte development or mucin secretion ( Powell et al, 2009 , 2011 ; Wang et al, 2020 ). A lack of a quadratic response may indicate that optimum tGly + Ser levels were not reached even at the highest level of added Gly from 0 to 48 d.…”
Section: Discussionmentioning
confidence: 69%